RASIO TEPUNG SAGU DAN IKAN MOTAN (Thynnichthys polylepis) TERHADAP KARAKTERISTIK KERUPUK - GUSLIKO NURMAN; USMAN PATO; YELMIRA ZALFIATRI (Universitas Riau, 2017)
Fish crackers are one of processed poducts with the fish as the main ingredient with addition of flour orstarch. This purpose of this study was to get the best ratio between sago starch and motan fish. This researchused a Complete Randomized Design Experiment with five treatments and three replications. The treatmentswere were the ratio of sago starch : motan fish 90:10 (K1), 80:20 (K2), 70:30 (K3), 60:40 (K4), 50:50 (K5). Thedata obtained were statistically analyzed using Analysis of Variance (ANOVA) and Duncan’s New MultipleRange Test (DNMRT) at 5% level. The parameters observed were swelling power, moisture, ash, and proteincontents as well as sensory test. Ratio of sago starch and motan fish significantly affected moisture, ash andprotein contents, colour, taste, aroma, crispiness, and acceptance by panelist. The best treatment of crackersfrom this research was K4 which had swelling power 21.57%, moisture content 11.90%, ash 0.97%, andprotein 22.00%. The result of descriptive test assessment, crackers had no brown colour (2.42), flavor fishcrackers (3.70), taste fish (3.72), and texture crispiness (2.57). Overall assessment hedonic test of crackerswas preferred by the panelists.